(untitled) (Canada, 2002)
Expanded to 2 volumes, Short Protocols in Molecular Biology, Fifth Edition, provides condensed descriptions of more than 700 methods compiled from Current Protocols in Molecular Biology. Includes new chapters on chromatin assembly and analysis, nucleic acid arrays, generation and use of combinatorial libraries, discovery and analysis of differentially expressed genes in single cells and cell populations. The book is specifically designed to provide quick access to step–by–step instructions for the essential methods used in every major area of molecular biological research Short Protocols in Molecular Biology, Fifth Edition is an authoritative and indispensable guide for all life scientists, researchers, and students at the graduate and advanced undergraduate level.
Ứng dụng công nghệ sinh học chăn nuôi
Keywords: Molecular biology,Molecular biology; Technique,Laboratory manuals